2019
DOI: 10.1021/acsomega.8b03647
|View full text |Cite
|
Sign up to set email alerts
|

Highly Porous Carbon Xerogels Doped with Cuprous Chloride for Effective CO Adsorption

Abstract: Carbon monoxide (CO) has long been recognized as a metabolic waste and toxic gas and is also the most common asphyxiating poison that seriously endangers human health. Thus, an adsorption material with high CO adsorption capability is urgently needed. In this study, carbon xerogels (CXs) doped with CuCl were prepared via a sol–gel method and a facile soaking process. The CuCl-doped CXs show the highest CO adsorption capacity of 12.04 cc/g, which is much higher than those of the undoped CXs and activated carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…On the surface of diatomite, CO is physically adsorbed via van der Waals force. In contrast, CO is chemically adsorbed on CuCl-modified diatomites via the interaction between Cu + ions and CO to form π-complexation bonds [15]. e Cu 2+ ions in the sample and CO are linked by the electrostatic bond and unable to form formation of the π-complexation bond [13].…”
Section: Carbon Monoxide Adsorption On Diatomite and Cucl-modified DImentioning
confidence: 99%
See 2 more Smart Citations
“…On the surface of diatomite, CO is physically adsorbed via van der Waals force. In contrast, CO is chemically adsorbed on CuCl-modified diatomites via the interaction between Cu + ions and CO to form π-complexation bonds [15]. e Cu 2+ ions in the sample and CO are linked by the electrostatic bond and unable to form formation of the π-complexation bond [13].…”
Section: Carbon Monoxide Adsorption On Diatomite and Cucl-modified DImentioning
confidence: 99%
“…Among many methods for CO removal, adsorption is widely used due to its high efficiency and lowcost treatment. Adsorbents for selective carbon monoxide adsorption such as metal-organic frameworks, zeolite, activated carbons, grapheme, and metal oxides have been reported in the literature [6][7][8][9][10][11][12][13][14][15]. Recently, Manh et al [13] reported that graphene oxide modified with Cu (I) showed much higher CO adsorption capacity than that of unmodified graphene oxide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, CO usually coexists with H 2 , CO 2 , CH 4 , N 2 , and H 2 O in the waste gas in actual production, , and CO should be separated and purified before it is applied. At the same time, CO is a toxic gas, , and CO could cause human body poisoning when its concentration reaches 0.02%; CO could cause explosion when its concentration increases to 12.5–74.2% . Additionally, when the concentration of CO exceeds 0.2 ppmv in the proton exchange membrane of the fuel cell, CO should make the platinum electrocatalyst damaged .…”
Section: Introductionmentioning
confidence: 99%
“…One of the most widely used methods for dealing with these toxic gases is to adsorb them using porous materials such as activated carbon (AC). For example, Park et al evaluated N 2 O adsorption by ACs and carbon molecular sieves (CMSs) at 293 K and 100 kPa, and the uptakes are 3.6 and 2.4 mol/kg, respectively . It was also reported that at a high temperature (423 K), the uptakes of SO 2 and CO by AC are 11.7 and 0.88 mg/g, respectively .…”
Section: Introductionmentioning
confidence: 99%